Transcriptome analysis of ciliary-dependent MCH signaling in differentiating 3T3-L1 pre-adipocytes - Laurie B. Cook (Nature Portfolio, 2021)
Abstract An understanding of adipocyte responsiveness to G-protein-coupled receptor-(GPCR) derived signals must take into consideration the role of membrane microenvironments; that individual sub-populations of proteins may vary significantly across different regions of the cell, and that cell differentiation alters those microenvironments. 3T3-L1 pre-adipocytes undergo a dramatic phenotypic transformation during differentiation into adipocytes, requiring the development of a transient primary cilium. We demonstrate that melanin-concentrating hormone (MCH) receptor 1, a GPCR that stimulates appetite, translocates to the transient primary cilium during early 3T3-L1 cell adipogenesis. Furthermore, we used RNA-Seq to investigate whether MCH signaling is influenced by its receptor localization and whether MCH can influence the transcriptome of early adipocyte development. We found that MCH signaling is sensitive to receptor localization to cilia, and this alters the adipogenic transcriptional program. Also, novel MCH signaling pathways in 3T3-L1 cells are identified, including those for circadian rhythm, the inflammatory response, and ciliary biogenesis. The presence of active MCH-signaling pathways in pre-adipocytes and the discovery that these pathways intersect with the early adipogenic program, among other newly-identified signaling pathways, suggests that the use of MCH receptor 1 antagonists for clinical interventions may have unintended consequences on adipose tissue development.